1996
DOI: 10.1149/1.1836548
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of In‐Se, Cu‐Se, and Cu‐In‐Se Thin Films

Abstract: Indium-selenium, copper-selenium, and copper-indium-selenium thin films have been prepared by electrodeposition techniques on molybdenum substrates. Electrodeposited precursors are prepared at varying potentials, pH, and deposition times. The adhesion and imiformity of indium selenide on molybdenum substrates are improved by electrodepositing an initial copper layer (500 A) on molybdenum. The films (In-Se, Cu-Se, and Cu-In-Se) are annealed at 250 and 450°C in Ar for 15 niln and are slow-cooled (3°C/mm). The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…InSe thin films were deposited from acidic aqueous solutions containing In 3+ and SeO 2 (or H 2 SeO 3 ) at potentials that ranged from −0.8 to −1.35 V vs. SCE [49][50][51][52][53][54][55] . The indium ions were from chloride 49,50,54,55) or sulfate [51][52][53] salts. In the deposition of InSe, the pH of the bath solution was below 1.7, 49,50,52,54,55) 2.4, 53) or 3.45.…”
Section: Potentiostatic Depositionmentioning
confidence: 99%
See 3 more Smart Citations
“…InSe thin films were deposited from acidic aqueous solutions containing In 3+ and SeO 2 (or H 2 SeO 3 ) at potentials that ranged from −0.8 to −1.35 V vs. SCE [49][50][51][52][53][54][55] . The indium ions were from chloride 49,50,54,55) or sulfate [51][52][53] salts. In the deposition of InSe, the pH of the bath solution was below 1.7, 49,50,52,54,55) 2.4, 53) or 3.45.…”
Section: Potentiostatic Depositionmentioning
confidence: 99%
“…The indium ions were from chloride 49,50,54,55) or sulfate [51][52][53] salts. In the deposition of InSe, the pH of the bath solution was below 1.7, 49,50,52,54,55) 2.4, 53) or 3.45. 51) Kampmann et al 53) performed the electrodeposition of InSe on an ITO substrate at −1.1 V vs. MSE and at 80 o C. Massaccesi et al 51) prepared In 2 Se 3 films on tin oxide substrates at 22 o C and 82 o C. Using XRD measurement, they observed that In 2 Se 3 films prepared at 82 o C had a better crystallinity than those obtained at 22 o C.…”
Section: Potentiostatic Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…A solar cell (Schottky type) employing a semi-transparent layer of Cu 2Àx Se as the window material on an n-type semiconductor is estimated to have excellent photovoltaic properties and a conversion ef®ciency of around 9% (Okimura et al, 1980). Many preparation methods of Cu 2Àx Se alloys have been reported, including sonochemical synthesis (Xu et al, 2002;Xie et al, 2002), chemical bath deposition (Garcia et al, 1999;Clement et al, 1997;Pathan et al, 2003), the photochemical route (Yan et al, 2003), -irradiation (Qiao et al, 2000), solid-state reaction (Danilkin et al, 2003), microwave-assisted heating (Zhu et al, 2000), a hydrothermal method (Wang et al, 1999), electrodeposition (Lippkow & Strehblow, 1998;Battacharya et al, 1996) and mechanical alloying (MA; Ohtani et al, 1995).…”
Section: Introductionmentioning
confidence: 99%